Moving by the spirit : Pentecostal social life on the Zambian Copperbelt - Haynes, Naomi (The anthropology of Christianity ;, 2017)
"This book argues that the runaway popularity of Pentecostal Christianity on the Zambian Copperbelt is a result of this religion's capacity to produce novel forms of value realization. A close analysis of the relationships that form in Pentecostal churches reveals that Pentecostal social life is structured around an animating idea - a value - called 'moving by the Spirit.' Moving by the Spirit entails personal advancement both with regard to material prosperity and religious skill or charisma. While moving by the Spirit makes Pentecostalism attractive, it is difficult for Pentecostal believers to balance prosperity against charisma without reproducing divisions in economic status. These divisions undermine the social world of the church by limiting the access of poorer believers to the relationships with their leaders - relationships through which the value of moving by the Spirit is most effectively realized"--Provided by publisher